Therapeutic Upper Gastrointestinal Endoscopy in Pediatric Gastroenterology - Schluckebier, Dominique; Afzal, Nadeem Ahmad; Thomson, Mike (Frontiers in Pediatrics, 2022)
This paper seeks to give a broad overview of pediatric upper gastrointestinal (GI) pathologies that we are now able to treat endoscopically, acquired or congenital, and we hope this delivers the reader an impression of what is increasingly available to pediatric endoscopists and their patients.